2021
DOI: 10.3390/jcm10194504
|View full text |Cite
|
Sign up to set email alerts
|

Successful Reversal of Severe Tachycardia-Induced Cardiomyopathy with Cardiogenic Shock by Urgent Rhythm or Rate Control: Only Rhythm and Rate Matter

Abstract: Background and objectives Severe forms of Tachycardia-induced cardiomyopathy (TIC) with cardiogenic shock are not well described so far, and efficiency of catheter ablation in this setting is unknown. Methods We retrospectively included consecutive patients admitted to the Intensive Cardiac Care Unit for acute heart failure with cardiogenic shock associated with atrial arrhythmia and managed by ablation. Result Fourteen patients were included, each with cardiogenic shock and two needing the use of extracorpore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The studies by Scheuermeyer et al, 17 Krothapalli et al 18 Hasbrouck and Nguyen 19 and Volle et al 20 provided less granular data. In the study by Scheuermeyer et al 17 118 of 416 patients (28%) presented to the ED with AFRVR and ADHF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies by Scheuermeyer et al, 17 Krothapalli et al 18 Hasbrouck and Nguyen 19 and Volle et al 20 provided less granular data. In the study by Scheuermeyer et al 17 118 of 416 patients (28%) presented to the ED with AFRVR and ADHF.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Volle et al 20 performed a retrospective study of consecutive patients admitted to the ICU for ADHF with cardiogenic shock associated with atrial arrhythmia and managed by AV nodal ablation. Although 60 patients presented with cardiogenic shock and atrial arrhythmias, only 14 were included in the analysis given the inclusion criteria of management by ablation.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to complications, arrhythmia, HF, and CGS are the three common complications of AMI [ 21 ]. Volle et al [ 22 ] indicated in their study that HF bore the main responsibility for morbidity and mortality in more than 10% of people over 70 years old, in addition to 10% of cases experiencing CGS immediately after the onset of AMI [ 23 ]. In our research, a statistically lower complication rate was found in the observation group as compared to the control group (9.09% vs. 25.56%), suggesting that PHEC for senile AMI patients is safer than conventional care, which is consistent with the report of Lihui and Qing [ 24 ] on the application of PHEC.…”
Section: Discussionmentioning
confidence: 99%
“…Any arrhythmia can be secondary to pre-existing underlying cardiomyopathy (e.g., ischemic or dilated cardiomyopathy) and thus a direct cause of the CS state or the other way around. Indeed, frequent arrhythmias [mainly atrial fibrillation (AF)] can ultimately lead to arrhythmia-induced cardiomyopathy and refractory CS ( 20 ). Reports on arrhythmia-induced CS are scarce and probably underrecognized, but Hékimian et al reported that CS was the first disease manifestation in 60% of their non-ischemic VA ECMO population with recent onset of supraventricular arrhythmia ( 21 ).…”
Section: Percutaneous Mcs Support During Arrhythmia-related Cardiogen...mentioning
confidence: 99%